2017
DOI: 10.4314/tjpr.v16i7.25
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lycium barbarum polysaccharide and synergism with paclitaxel/cisplatin in ovarian cancer in mice

Abstract: Purpose: To determine the efficacy of Lycium barbarum polysaccharide (LBP) in ovarian cancer, and the synergistic effect when used in combination with paclitaxel/cisplatin (PXT∕DDP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…67,68 Although such techniques have yet to be applied to LB, research using various multi-component LB extracts is ongoing. Synergism with other drugs, such as paclitaxel/ cisplatin in the treatment of ovarian cancer, 69 interferon-α2b in renal cell carcinoma, 70 and others, has also been observed.…”
Section: Composition: Single Component Versus Synergistic Blends In Rmentioning
confidence: 94%
“…67,68 Although such techniques have yet to be applied to LB, research using various multi-component LB extracts is ongoing. Synergism with other drugs, such as paclitaxel/ cisplatin in the treatment of ovarian cancer, 69 interferon-α2b in renal cell carcinoma, 70 and others, has also been observed.…”
Section: Composition: Single Component Versus Synergistic Blends In Rmentioning
confidence: 94%
“…Animals experiments have demonstrated that NPs from herbs could regulate Nrf2 antioxidant pathway for liver protection ( 14 , 36 , 41 , 54 , 57 , 67 , 116 , 120 , 147 153 ), kidney protection ( 21 , 59 , 154 157 ), lung protection ( 20 , 158 ), neuroprotection ( 22 , 121 ), cardioprotection ( 124 , 159 ), gastrointestinal protection ( 16 , 40 , 48 , 127 , 128 , 160 , 161 ), anti-oxidation ( 15 , 47 , 162 164 ), anti-diabetic ( 56 , 58 , 135 , 146 , 165 , 166 ), anti-aging ( 18 , 68 , 84 , 167 ), anti-inflammation ( 23 ), anti-depression ( 25 ), anti-cancer ( 168 ), and improving reproductive function ( 169 , 170 ), as implied in Table 1 .…”
Section: Regulation Of Nps On Nrf2 Antioxidant Pathway For Health-pro...mentioning
confidence: 99%
“…Lycium barbarum polysaccharide revealed anti-inflammation against cerulein-induced mice by adding nuclear Nrf2 protein expression and HO-1 activity in pancreas ( 23 ). Meanwhile, this polysaccharide implied anti-cancer action against ID-8 cells bearing-mice through up-regulation of mRNA and protein expressions of Keap1, Nrf2 and HO-1 in liver and kidney tissues ( 168 ). Polygonatum cyrtonema polysaccharide had anti-depression activity on LPS and CUMS-induced mice via increasing protein expressions of Nrf2 and HO-1 in hippocampal tissues ( 25 ).…”
Section: Regulation Of Nps On Nrf2 Antioxidant Pathway For Health-pro...mentioning
confidence: 99%